In vivo evidence of cortical amyloid deposition in the adult form of Niemann Pick type C. Issue 11 (November 2019) - Esposito, Marcello; Dubbioso, Raffaele; Tozza, Stefano; Iodice, Rosa; Aiello, Marco; Nicolai, Emanuele; Cavaliere, Carlo; Salvatore, Marco; Santoro, Lucio; Manganelli, Fiore
Abstract: Background: Niemann Pick disease type C (NPC) is a lysosomal lipid storage disorder presenting visceral and neurological impairment with cognitive decline. Neurodegeneration in NPC is associated to deposition of amyloid-β and abnormal tau aggregations likewise Alzheimer disease (AD). Dementia is also related to intracortical circuiting abnormalities that can be detected by neurophysiological procedures both in NPC and in AD. Aim of this study is to find the in vivo evidence of amyloid deposition in NPC patients with cognitive impairment and to investigate the pathophysiology of dementia according to similarities with AD. Methods: Two sisters affected by NPC and cognitive decline underwent neuropsychological tests, PET scans with 18 F- Florbetaben and neurophysiological protocols to assess cortex excitability by means of transcranial magnetic stimulation (TMS), such as short-latency afferent inhibition (SAI), short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF). Results: Both patients presented a multidomain cognitive impairment. 18 F- Florbetaben uptake was detected in brain frontal areas, while SAI and SICI were abnormal in both patients. Discussion: Cognitive impairment in NPC is associated to cortical amyloid deposition as revealed by 18 F- Florbetaben PET scan. Amyloid imaging data, together with specific abnormalities found at TMS studies, suggest similar mechanisms underlying NPC and AD dementia. Abstract : Medical imaging, Neurology, Nuclear medicine, Neuroscience, Physiology, Nervous system; Radiology; PET-MRI; Niemann-pick type C disease; Amyloid; TMS.; Alzheimer disease; Cognitive impairment